Rapid Rise in Hypertension and Nephropathy in Youth With Type 2 Diabetes: The TODAY clinical trial (American Diabetes Association, 2013)
OBJECTIVE: Among adolescents with type 2 diabetes, there is limited information regarding incidence and progression of hypertension and microalbuminuria. Hypertension and microalbuminuria assessments made during the TODAY clinical trial were analyzed for effect of treatment, glycemic control, sex, and race/ethnicity. RESEARCH DESIGN AND METHODS: A cohort of 699 adolescents, 10–17 years of age, <2 years duration of type 2 diabetes, BMI ≥85%, HbA(1c) ≤8% on metformin therapy, controlled blood pressure (BP), and calculated creatinine clearance >70 mL/min, were randomized to metformin, metformin plus rosiglitazone, or metformin plus intensive lifestyle intervention. Primary study outcome was loss of glycemic control for 6 months or sustained metabolic decompensation requiring insulin. Hypertension and microalbuminuria were managed aggressively with standardized therapy to maintain BP <130/80 or <95th percentile for age, sex, and height and microalbuminuria <30 μg/mg. RESULTS: In this cohort, 319 (45.6%) reached primary study outcome, and 11.6% were hypertensive at baseline and 33.8% by end of study (average follow-up 3.9 years). Male sex and higher BMI significantly increased the risk for hypertension. Microalbuminuria was found in 6.3% at baseline and rose to 16.6% by end of study. Diagnosis of microalbuminuria was not significantly different between treatment arms, sex, or race/ethnicity, but higher levels of HbA(1c) were significantly related to risk of developing microalbuminuria. CONCLUSIONS: Prevalence of hypertension and microalbuminuria increased over time among adolescents with type 2 diabetes regardless of diabetes treatment. The greatest risk for hypertension was male sex and higher BMI. The risk for microalbuminuria was more closely related to glycemic control.